Population decline in the critically endangered Musschia isambertoi (Campanulaceae) endemic to Desertas Islands (Madeira Archipelago) calls for urgent conservation management - Sequeira, M. Menezes de (2022)
Macaronesian islands display a high degree of plant endemicity and correspond to some of the most threatened biodiversity hotspots due to several human driven impacts such as habitat loss, invasive species, overexploitation or climate change. The conservation status of the largest of the two known population of Musschia isambertoi M. Seq., R. Jardim, Magda Silva and L. Carvalho (Campanulaceae) was assessed recently. Field work was done in June 2018 in “Porto das Moças” Deserta Grande (Madeira Archipelago, Portugal), the locus typicus, where in 2006 close to 30 plants were detected with a high variation of age/size between individuals comprising both fully flowering and non-flowering adult plants as well as seedlings, and thus corresponding to a healthy population. This study assesses population size, age and plant size, and genetic, as well as floristic diversity. The total area of the site corresponds to approximately 1500 square meters. Ten individuals were detected, all corresponding to young seedlings not exceeding 15 cm high, and exhibiting approximately the same size and numbers of leaves (4–8). No adult plants or remains of adult plants were seen. Ecological data and direct herbivory evidence suggest that perennial plants are subjected to elimination during the short summer by the feral goat population. Mo lecular data based on ISSR markers show that the nine sampled individuals (out of ten individuals found) are genetically identical, possibly resulting from one parental plant. Results clearly suggest that Musschia isambertoi is very close to extinction. Urgent conservation measures are imperative and should include the immediate fencing of the population followed by the elimination of feral goats from Deserta Grande. The elimination of feral goats was initiated in 1996 (LIFE95 NAT/P/000125, 383,467.00 €) but stopped due to inappropriate conser vation policies of the former Services of the Natural Park of Madeira.